Symbolic and Philosophical Meanings of Religion and Politics in Hamzanwadi's Wasiat Renungan Masa Pengalaman Baru: A Semiotic Perspective - Wijaya, Herman; Fakihuddin, Lalu; Ernawati, Titin; H.A. Gani, Ramlah. (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
This study aims to uncover the symbolic and philosophical meanings of religion and politics in Hamzanwadi's Wasiat Renungan Masa Pengalaman Baru. This research employs qualitative methods with a semiotic approach in analysing the poem's verses containing religious and political symbolism. Data collection involved close reading, interpretation, and in-depth understanding of the verses, while semiotic analysis was applied to identify and examine the symbols and their philosophical meanings. Several steps in data validation include reduction, presentation, and conclusion drawing.The results reveal that Hamzanwadi employs religious and political symbols in his poem to convey moral and social messages. Religious symbols—such as faith, piety, and the concept of the Almighty God—highlight the importance of loyalty and commitment to religious values in political life. Political symbols—such as seats and positions—represent political ambitions that can threaten religious teachings' integrity and true purpose. The philosophy embedded in these symbols emphasises the significance of loyalty, integrity, and honesty in politics and warns against using religion for personal or political gain.This research offers key insights into three main points: 1) faith and piety serve as a solid moral foundation for ethics inpolitical life; 2) political ambition and power have the potential to corrupt religious values and undermine integrity; and 3) integrity and adherence to religious teachings are essential for promoting clean and responsible governance. These findings contribute to a deeper understanding of the interaction between religion and politics in Hamzanwadi's workand offerbroader reflections on ethical leadership.